Pengembangan Life Skill Perempuan Lewat Pengelolaan Sampah di Bokoharjo, Sleman - Punik Mumpuni Wijayanti; Utami Utami (SiRad: Pelita Wawasan, 2025)
At the end of the 21st century, various community empowerment programs have emerged, focusing on environmental sustainability due to increasing environmental degradation and growing awareness of the need for conservation. Indonesia, as the world's second-largest food waste producer in 2021 according to The Economist Intelligence Unit, faces significant waste management challenges.Environmental issues are also linked to ecofeminism, where women play an active role in environmental preservation to create an eco-friendly and women-friendly society. Therefore, this program aims to support women in waste management, enhancing their awareness and concern for environmental sustainability. Bokoharjo Village, where women make up approximately 50% of the total population, has been chosen as the target location to optimize their creativity in waste management, particularly in tourist areas. The program includes condition analysis, increasing women's involvement in household waste management, empowering economically unproductive communities, and fostering partnerships with relevant stakeholders.The program employs a women’s empowerment approach through training and mentoring. The outcomes include the publication of an accredited journal and the development of an independent household waste management system. This initiative has successfully improved women's life skills in household management, creativity, and entrepreneurship. By transforming waste into economically valuable products, women in Bokoharjo can enhance their family income while contributing to environmental conservation. Additionally, the program strengthens women's roles as agents of change within their families and communities, leading to improved well-being and environmental awareness. [Di akhir abad ke-21, muncul berbagai program pemberdayaan masyarakat yang berfokus pada lingkungan akibat meningkatnya kerusakan alam dan kesadaran akan pentingnya keberlanjutan. Indonesia, sebagai penghasil sampah makanan terbesar kedua di dunia pada 2021 menurut The Economics Intelligence Unit, menghadapi tantangan besar dalam pengelolaan limbah.Isu lingkungan juga berkaitan dengan ekofeminisme, di mana perempuan berperan aktif dalam menjaga kelestarian alam demi terciptanya kehidupan yang eco-friendly dan women-friendly. Oleh karena itu, program ini bertujuan mendampingi perempuan dalam pengelolaan sampah guna meningkatkan kesadaran dan kepedulian mereka terhadap lingkungan.Kalurahan Bokoharjo, dengan penduduk perempuan sekitar 50% dari total populasi, menjadi sasaran program ini untuk mengoptimalkan kreativitas mereka dalam mengelola sampah, terutama di kawasan wisata. Program ini meliputi analisis kondisi, peningkatan peran perempuan dalam pengelolaan sampah rumah tangga, pemberdayaan masyarakat tidak produktif secara ekonomi, serta kolaborasi dengan mitra. Metode yang digunakan dalam program ini adalah pemberdayaan perempuan melalui pelatihan dan pendampingan. Hasil dari program ini meliputi penerbitan jurnal terakreditasi dan pengembangan sistem pengelolaan sampah rumah tangga mandiri.Program ini telah berhasil meningkatkan keterampilan hidup (life skill) perempuan dalam manajemen rumah tangga, kreativitas, dan kewirausahaan. Dengan mengolah sampah menjadi produk bernilai ekonomi, perempuan di Bokoharjo mampu meningkatkan penghasilan keluarga sekaligus berkontribusi pada pelestarian lingkungan. Selain itu, program ini juga memperkuat peran perempuan sebagai agen perubahan di keluarga dan komunitas, yang berdampak pada peningkatan kesejahteraan dan kesadaran lingkungan.]